Future‑ready workforce: a 2023–2024 literature review of essential skills and competencies for the labor market - Joanna Zukowska; Karolina Lemieszkiewicz (Przedsiębiorczość - Edukacja, 2025)
Objective: The purpose of this study is to identify both the skills and competencies desired in the labor market. The paper’s aim will be to point out what skills and competencies are required and to define trends in the coming years in terms of qualifications and skills.Research Design & Methods: A literature review method has been used, identifying and reviewing existing academic works in the field. The Scopus database was used with an applied timeframe of 2023–2024. Findings: More than 40 skills and competencies were identified divided into three main groups. The results revealed trends observed in the labor market and the research provides the framework of skills and competencies. Implications & Recommendations: The study’s results highlight emerging competency gaps, providing valuable insights for the education sector to develop the necessary soft and hard skills of employees. For companies, it offers guidance on essential skills and competencies for employee development, training strategies and career planning.